2023
DOI: 10.1007/s00240-023-01440-8
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and molecular characterization of calcium oxalate stone formers predicting occurrence and recurrence

Abstract: The purpose of the study is to investigate the role of sex hormones, androgen receptors (ARs) and miRNA/CSF-1 in occurrence and recurrence of calcium oxalate (CaOx) renal urolithiasis. In this prospective study, 74 patients with CaOx stones; stone formers group (SFG) and 40 healthy subjects; control group were compared. SFG includes both de novo and recurrent cases. Steroid sex hormone plasma assay including testosterone, free testosterone, dihydrotestosterone, estradiol, and sex hormone binding globulin was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, CSF-1 expression was significantly lower in the stone group than in the healthy subjects. Wei Zhu et al showed that inhibition of androgen receptor (AR) expression in renal tubular epithelial cells increased macrophage recruitment/M2 polarization, which resulted in enhanced phagocytosis of CaOx crystals in the kidney, confirming that estrogens inhibit the formation of stones more than androgens do in the human body [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CSF-1 expression was significantly lower in the stone group than in the healthy subjects. Wei Zhu et al showed that inhibition of androgen receptor (AR) expression in renal tubular epithelial cells increased macrophage recruitment/M2 polarization, which resulted in enhanced phagocytosis of CaOx crystals in the kidney, confirming that estrogens inhibit the formation of stones more than androgens do in the human body [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CSF-1 expression was signi cantly lower in the stone group than in the healthy subjects. Wei Zhu et al showed that inhibition of androgen receptor (AR) expression in renal tubular epithelial cells increased macrophage recruitment/M2 polarization, which resulted in enhanced phagocytosis of CaOx crystals in the kidney, con rming that estrogens inhibit the formation of stones more than androgens do in the human body (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…AR can decrease Mp colony-stimulating factor 1 (CSF-1) expression by increasing miRNA-185-5p expression to suppress M2 Mp polarization-mediated intrarenal CaOx crystal phagocytosis [72]. In a prospective study, Elshal et al found that patients (n = 74) with CaOx stones had a higher expression of ARs and miRNA-185-5p compared with healthy individuals (n = 40), while CSF-1 expression was lower in stone formers [73]. These findings suggest that the signaling pathways of AR, miRNA, and CSF-1 are significant factors in the development of kidney stones.…”
Section: Macrophage Polarization and Metabolismmentioning
confidence: 99%
“…Some non-coding RNAs have altered expression profiles in kidney stones and may have the potential as biomarkers to aid in the diagnosis of kidney stones and to assess the extent of kidney damage and recovery after treatment [23,24,73,94]. However, none of the non-coding RNAs are currently used as routine tests for kidney stone patients.…”
Section: Non-coding Rnas As Biomarkers For Kidney Stonementioning
confidence: 99%
See 1 more Smart Citation